1998
DOI: 10.1073/pnas.95.2.565
|View full text |Cite
|
Sign up to set email alerts
|

UVB-induced association of tumor necrosis factor (TNF) receptor 1/TNF receptor-associated factor-2 mediates activation of Rel proteins

Abstract: Exposure of mammalian skin to UV light results in induced gene transcription, playing a role in inf lammation, immunosuppression, and tumor promotion. One important group of transcription factors induced by UV radiation is composed of members of the Rel͞NF-B family, which are known to play a major role in the transcriptional activation of many genes encoding inf lammatory cytokines, adhesion molecules, and viral proteins. However, the upstream events in the transduction of the UVB signal to Rel protein activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…All three of these gene biomarkers were significantly decreased with R-equol and/or racemic equol compared to S-equol. Looking at other aging genes, the FOS (immediate early) biomarker is known to protect against photoaging while TNFRSF1A is involved with UV-induced DNA damage via sun exposure or photoaging (Tobin et al, 1998;Tomicic et al, 2011). The highest levels of FOS gene expression were seen with racemic equol.…”
Section: Discussionmentioning
confidence: 99%
“…All three of these gene biomarkers were significantly decreased with R-equol and/or racemic equol compared to S-equol. Looking at other aging genes, the FOS (immediate early) biomarker is known to protect against photoaging while TNFRSF1A is involved with UV-induced DNA damage via sun exposure or photoaging (Tobin et al, 1998;Tomicic et al, 2011). The highest levels of FOS gene expression were seen with racemic equol.…”
Section: Discussionmentioning
confidence: 99%
“…An initial step in UV-induced photocarcinogenesis is the formation of potentially mutagenic DNA damage in skin cells. In addition, UVB may induce changes in the expression of many genes (Tobin et al, 1998) and trigger the release of various cytokines from human keratinocytes, e.g., IL-6, TNF-a, IL-1, IL-10, and IL-12 (Kondo and Jimbow, 1998;EberleinKonig et al, 1998;Soriani et al, 1999). These cytokines may provide the growth advantages for the initiated or mutant skin cells, which, in turn, enhance the development of skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, UV-irradiation has been shown to activate NF-kB in enucleated cells (Devary et al, 1993); a ®nding which rules out nuclear DNA damage as a trigger in some of the UV-mediated e ects. Tobin et al (1998), have recently reported that UV activation of Rel/NF-kB appears to occur via TNFR1. UV-induced multimerization and activation of TNFR1 has also been shown and was implicated in UV stimulation of JNK activation (Rosette and Karin, 1996).…”
Section: Introductionmentioning
confidence: 99%